Pengembangan Fitur Manajemen Artis dan Sales pada Aplikasi Penjualan Musik Berbasis Web (Insan Music Store) - Endang Amalia; Muhammad Rosyid (CV. Multi Kreasi Media, 2022)
With the rapid development of digital, every aspect of life adapts to today's digital habits. The music world is no exception, where digital sales of musicians' works are one of their most significant income sources. Created to help musicians conduct their work in the form of music, Insan Music Store continues to strive to meet every need of the music industry, especially indie music. With the more straightforward process of joining the Insan Music Store application, it is hoped that it will attract the interest of musicians to join the Insan Music Store as a means of promotion for their work. This development is based on a questionnaire distributed to musicians and customers who have registered with the Insan Music Store regarding their problems and experiences while using the Insan Music Store application. The application development process itself uses the Python programming language using the framework from Django, with a database using PostgreSQL. As of the development tools used by developers is Visual Studio Code.